Thermochemical energy storage in SrCO3 composites with SrTiO3 or SrZrO3 - Williamson, Kyran; Liu, Yurong; Humphries, Terry; D'Angelo, A.M.; Paskevicius, Mark; Buckley, Craig (2024)
Thermochemical energy storage offers a cost-effective and efficient approach for storing thermal energy at high temperature (∼1100 °C) for concentrated solar power and large-scale long duration energy storage. SrCO3 is a potential candidate as a thermal energy storage material due to its high energy density of 205 kJ/mol of CO2 during reversible CO2 release and absorption. However, it loses cyclic capacity rapidly due to sintering. This study determined that the cyclic capacity of SrCO3 was enhanced by the addition of either reactive SrTiO3 or inert SrZrO3, where the molar ratios of SrCO3 to SrZrO3 were varied from 1:0.125 to 1:1. Thermogravimetric analysis over 15 CO2 sorption cycles demonstrated that both materials retained ∼80 % of their maximum cyclic capacity on the milligram scale. Repeated measurements using gram scale samples revealed a decrease in maximum capacity to 11 % using a sample of SrCO3 – 0.5 SrZrO3 over 53 cycles, while the use of SrTiO3 additives allowed for the retention of 80 % maximum capacity over 55 cycles. These findings highlight the potential of reactive additives in enhancing the performance of thermochemical energy storage systems, while providing valuable insights for the development of cost-effective materials.